Method for the Analysis of Tissue Oxygen Saturation Disorders Using an Optical Analyzer of Visible and IR Spectra - Naumova, Victoria; Kurkova, Alexandra; Davydov, Roman; Zaitceva, Anna (IEEE International Conference on Electrical Engineering and Photonics (Online), 2022)
Every year the issue of the use of non-invasive diagnostic methods in medicine is becoming more and more relevant. One of the significant directions is the development of optical methods for monitoring blood filling of human limbs using a multichannel spectrum analyzer. Deviations in the status of blood flow in the vessels of the extremities recognized by optical methods can be associated with the development of many dangerous pathologies. The analysis of the measurement results recorded by the optical system of the subjects at rest, when performing physical exertion, revealed various trends in the change of blood filling of the limbs before and after exercise tests. Groups of subjects with different responses to functional load in the form of an occlusive test were obtained, the results were visualized, which allowed revealing hidden patterns in the change in blood filling of the limbs according to the indications of optical sensors at various points in the experiment. The results are presented, indicating the possibility of automated detection of deviations from the norm of the parameters of blood filling of the extremities.